The Tailored Implementation in Chronic Diseases (TICD) project: introduction and main findings. (December 2017) - Wensing, Michel
Abstract Background The Tailored Implementation in Chronic Diseases (TICD) project aims to contribute knowledge on how to improve healthcare for patients with chronic diseases and, at the same time, knowledge on concepts and methods of tailoring interventions to local conditions. In this contribution, the project is briefly introduced and its main findings are discussed. Discussion The tailored implementation programs in the TICD project had little impact, for which we provide a range of potential explanations. Structured group interviews with informed stakeholders, such as clinicians and researchers, were used to generate perceived determinants of practice and suggestions for tailored implementation strategies. They were productive and valid, yet incomplete, if compared to perceptions of healthcare providers who received the tailored implementation programs. Ongoing monitoring of determinants of practice during intervention delivery seems required to adapt the interventions to emerging needs and opportunities.